Association among Clopidogrel Cessation, Platelet Function, and Bleeding in Coronary Bypass Surgery: An Observational Trial - Petricevic, Mate; Knezevic, Jadranka; Biocina, Bojan; Mikus, Mislav; Konosic, Lucija; Rasic, Mario; Milosevic, Milan; Rotim, Cecilija; Madzar, Tomislav; Rotim, Ante; Gasparovic, Hrvoje; Goerlinger, Klaus (The Thoracic and Cardiovascular Surgeon, 2019)
Objectives This study sought to determine (1) the association between the length of preoperative clopidogrel discontinuation, blood loss, and transfusion requirements and (2) whether preoperative platelet function testing predicts excessive postoperative bleeding in patients undergoing coronary artery bypass grafting (CABG) surgery.Methods In this retrospective analysis, patients undergoing CABG were divided into three groups with regard to the period between preoperative clopidogrel cessation and surgery: group 1 (n = 94, ≤3 days), group 2 (n = 100, 4–5 days), and group 3 (n = 83, 6–7 days), respectively. Impedance aggregometry (Multiplate) with arachidonic acid (ASPI) test assay (used for platelets stimulation) and adenosine diphosphate (ADP) test (used for platelets stimulation) was performed before the surgery. Primary outcome was 24 hours chest tube output (CTO) and transfusion requirements (red blood cell concentrate [RBCC], platelet concentrate [PC], fibrinogen concentrate [FC], and fresh-frozen plasma [FFP]) were considered as secondary outcomes.Results CTO during 24 hours was significantly higher in group 1 as compared with groups 2 and 3, respectively (p = 0.003). Considering secondary outcomes, RBCC (p = 0.043), PC (p = 0.001), FC (p = 0.003), and FFP (p = 0.010) were more frequently transfused in group 1 as compared with groups 2 and 3, respectively. Multiple electrode aggregometry ASPI and ADP tests were significantly correlated with the 24-hour CTO (ASPI test—rho = −0.258, p < 0.001; ADP test—rho = −0.164, p = 0.007). A significant correlation was observed between clopidogrel-free interval and 24-hour CTO (rho = −0.200, p < 0.001). Receiver-operating characteristics (ROC) curve analysis revealed cutoff values to delineate bleeding tendency (ASPI test ≤ 25 area under the aggregation curve [AUC], ADP test ≤63 AUC, and clopidogrel-free interval ≤3 days).Conclusion Excessive postoperative bleeding occurred less frequently if the period between clopidogrel discontinuation and surgery was longer than 3 days, as compared with shorter waiting time. Inadequate recovery of the platelets function following clopidogrel cessation in preoperative period was associated with increased bleeding risk. Platelet function testing was found to be a useful tool for postoperative bleeding management in our hands.
Keywords: coronary artery bypass grafting; multiple electrode aggregometry; antiplatelet; drugs; clopidogrel; transfusion